The Influence of Internal Control Systems, Whistleblowing Systems, and Organizational Culture on Fraud Prevention at PT Triana Harvestindo Nusantara - Linda, Linda; Nurfauziah, Farah Latifah; Suharti, Sri (Journal of Accounting Auditing and Business, 2025)
The increasing frequency of fraud cases in the industrial sector, including textiles, reflects the insufficient implementation of internal controls, whistleblowing mechanisms, and ethical organizational culture. Internal actors both individuals and groups are often responsible, underscoring the need for a systematic approach to prevention. This study examines the influence of internal control systems, whistleblowing systems, and organizational culture on fraud prevention at PT Triana Harvestindo Nusantara. Using a quantitative, causally associative method, data were gathered from 200 employees through structured questionnaires and analyzed via SPSS version 25. Results indicate that all three variables significantly contribute to mitigating fraud risk. The findings suggest that reinforcing internal controls, promoting secure reporting channels, and embedding integrity within the corporate culture are essential to reducing fraudulent activities.Keywords: Internal Control System, Whistleblowing System, Organizational Culture, Fraud Prevention.